Knowledge, attitudes, and practices of junk food consumption among normal bmi and overweight/obese undergraduate health science students in USM Health Campus - Ridzuan, Nurdini Athirah Ahmad (Universiti Sains Malaysia, 2024)
Young people consume more junk food than older individuals. University students in developing countries increasingly consume junk food as a major part of their diet. Busy university life often leaves little time for meal planning and preparation, leading students to choose the convenience of junk food. These foods are high in fat, sugar, salt, calories, and artificial colors but low in nutrition, posing health risks. This study aimed to evaluate the knowledge, attitudes, and practices (KAP) regarding junk food consumption among health science students with normal and overweight/obese body mass index (BMI) statuses. It also explored the relationship between KAP scores and sociodemographic characteristics. A cross-sectional approach was used, involving 107 health science students. Participants completed an online questionnaire accessed through a QR code after their weight and height were measured. Results showed that 50.5% of respondents had a normal BMI, while 49.5% were overweight/obese. The study found that participants had high knowledge about junk food, negative attitudes towards it, but still engaged in high consumption. Comparing KAP levels between normal and overweight/obese students, the study found no significant difference in knowledge and attitudes between the two groups. However, there was a significant difference in practice scores, with students of normal BMI showing higher practice scores compared to overweight/obese students. Additionally, there was no significant relationship between knowledge, attitude, and practice towards junk food consumption for both groups. In conclusion, health science students, despite being aware of the negative effects of junk food, do not always translate this knowledge into healthier eating habits, especially among those who are overweight or obese. To effectively reduce junk food consumption, interventions should focus not only on increasing awareness but also on changing attitudes and behaviors to promote healthier eating habits among university students.